Use of Statistical Quality Control in Experimental Procedures for Mechanical Properties Determination of Vegetative Tissues - Jonathan Gazzola; Angelo Roberto Biasi; Leandro Morais; Kelen Cristiane Cardoso; Daniel Albiero; Inacio Maria Dal Fabbro (Revista Ciência Agronômica)
ABSTRACT Vegetative tissues are viscoelastic materials and suffer from internal and external interferences to obtain data for the characterization of their mechanical properties. Quality control tools are likely to detect internal and external problems in processes and indicate anomalies in the system or sampling points analyzed. This research aims to analyze the use of quality control tools to detect problems in experimental procedures and in sampling data to determine mechanical properties of plant tissues. Uniaxial compression tests were performed to determine the modulus of elasticity and tensile strength under three compression ratios of 0.2 mm/s, 0.4 mm/s, and 0.6 mm/s. Shewart individual and moving range charts were used to analyze internal and external problems, respectively, obtained in the MINITAB software. The results showed that the quality control charts were able to detect sample points that negatively impacted the characterization data.